Theatrum Orbis Librorum : Liber amicorum Presented to Nico Israel on the Occasion of his Seventieth Birthday - Horst, K. van der; Schilder, G.; Uchelen, T. Croiset van (European History and Culture - Book Archive pre-2000., 1989)
With contributions on geography, travel, rare books, booktrade, collectors and libraries by C. Koeman, G. Schilder, R. Breugelmans, K. van der Horst, F.A. Janssen, C. Reedijk, J. Storm van Leeuwen, E. Braches, E. Cockx-Indestege, I.H. van Eeghen, H. de la Fontaine Verwey, L. Hellinga-Querido, P.F.J. Obbema, B. van Selm, a.o